Profil Karakteristik Peternakan Sapi Potong di Daerah Dataran Rendah (Studi Kasus di Desa Nonotbatan Kecamatan Biboki Anleu Kabupaten Timor Tengah Utara) - Nailape, Merliana Kolo; Sahala, Josua; Usboko, Nofriana; Feka, Wolfhardus Vinansius; Banu, Marselinus; Usboko, Novriana; Manek, Humbelina Fega (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study: 1). to determine the characteristics of beef cattle breeders. 2). the beef cattle maintenance system in Nonotbatan Village, Biboki Anleu District, North Central Timor Regency. This study was conducted in August-September 2024 in Village Nonotbatan, Biboki Anleu District, North Central Timor Regency. The method used is a survey method using quantitative descriptive analysis techniques to collect secondary data and primary data from respondents. This study used a purposive sampling technique and the variables observed were characteristics based on age, gender, ownership status, number of livestock, occupation, livestock experience, number of family dependents, monthly income, land ownership. The results of this study are the profile of the characteristics of beef cattle farming in lowland areas (Case Study in Nonotbatan Village, Biboki Anleu District, North Central Timor Regency) based on the age of the farmers, most of them are over 60 years old (29.4%), gender is generally 93.5% male, education level is mostly elementary school graduates (66.7%), livestock ownership status is 100% owned by themselves, the average number of livestock is 66.6%, the most is 2-5 heads, the main job is 97.4% as farmers, livestock experience is 71.8% on average ≥5 years, monthly income is mostly 55.1%, namely IDR 0-250/month, average land ownership is ≥0.50 Ha, namely 66.7%, the number of family dependents is mostly 4-6 people, namely 62.8%, The livestock maintenance system is semi-intensive for 68 people (87.2%).